Determinants of Diabetes Mellitus Type-2 in Integrated Guidance Post for Non-Communicable Diseases Participants in Jayapura - Natalia Paskawati Adimuntja; Asriati (Universitas Mandala Waluya, 2023)
The prevalence of Diabetes Mellitus in Indonesia in 2018 based on an examination of blood sugar levels in residents 15 years old is 8.5%, while in Papua, doctors diagnosed with a population aged 15 years are 1.1%. The purpose of this study is to determine the factors associated with type 2 diabetes mellitus in Non-Communicable Diseases (NCDs) Integrated Guidance Post participants at the Kotaraja Health Center, Jayapura City. This type of research is an observational study with a cross-sectional study design. The population of the study was people aged >15 years in the working area of the Kotaraja Health Center who visited the NCDs Integrated Guidance Post. The sample of this study was all participants of the Integrated Guidance Post of the NCDs with a total of 52 people. The sampling technique is total sampling. Statistical test using chi-square test. As many as 7 people (13.5%) of Integrated Guidance Post participants had type 2 DM and 45 people (86.5%) did not have type 2 DM. The results of the statistical analysis found age (p-value= 0.04), as well as fruit and vegetables (p-value= 0.004), had a relationship with the incidence of type 2 DM in Integrated Guidance Post of the Non-Communicable Diseases participants at the Kotaraja Health Center with a p-value <0.05. Factors related to the incidence of type 2 DM in NCDs Integrated Guidance Post participants at the Kotaraja Health Center were age and fruit and vegetable consumption. The active role of cadres and health workers in educating and screening the community is an effort to prevent and control Non-Communicable Diseases in the community.